A Proven Case of Cutaneous Rhizopus Infection Presenting with Severe Limb Pain Very Soon after Induction Treatment in a Patient with Acute Lymphoblastic Leukemia - Mehmet Sezgin Pepeler; Kadir Acar; Özlem Güzel Tunçcan; Ömer Uluoğlu; Ayşe Kalkancı; Hakan Atalar; Koray Kılıç; Gülsan Türköz Sucak (Case Reports in Hematology)
Objective and Importance. Invasive mucormycosis may complicate the course of patients with hematologic malignancies and has a very high mortality rate. Early diagnosis and aggressive approach combined with surgical and medical treatment have paramount importance for cure. Clinical Presentation. We report here a case of a patient with acute lymphoblastic leukemia presenting with a subcutaneous mass lesion which was sampled by an ultrasound guided needle biopsy. The pathology showed microorganisms with aseptate hyphae with wide, irregular walls and more or less branching with highly vertical angles which suggested a mold infection. The specimen was also cultured where Rhizopus spp. grew. Conclusion. Posaconazole 200 mg QID was commenced. She recovered from neutropenia and pain on day 20 of treatment. After 4 courses of hyper-CVAD chemotherapy, the remaining soft tissue mass was removed surgically and she underwent allogeneic HSCT from a full matched sibling donor under secondary prophylaxis.